PHYTOCHEMICAL SCREENING AND FREE RADICAL SCAVENGING ACTIVITIES OF METHANOL LEAF AND FLOWER EXTRACT OF Securidaca longipedunculata - Shemishere, U. B.; Anyebe, D. A; Bashir, A. Y; Emmanuel, J.; Ifie, J.; Yahaya, T (FUDMA JOURNAL OF SCIENCES, 2020)
Securidaca longipedunculata is one of the known medicinal plants in Africa belonging to the Polygalaceae family. The objective of this study was to investigate the phytochemical contents as well as the free radical scavenging properties of methanol leaf and flower extract of the plant. The plant material was extracted using methanol for 72 hours. Extraction yielded 24.432% and 19.88% (w/w) of leaf and flower respectively. The preliminary phytochemical screening for leaf extract revealed the presence of phenols, tannins, flavonoids, saponins, glycosides, steroids, terpenoids, quinones and fixed oil while alkaloids, coumarin and xanthoproteins were not detected. The flower extract showed the presence of alkaloids, tannins, flavonoids, terpenoids and phenols while steroids and saponins were absent. The leaf and flower extracts revealed significant DPPH free radical scavenging activity. The total flavonoid content of leaf extract was found to be 17.0867 ± 0.268 mg Quercetin Equivalent/g extract while total phenolics content was found to be 22.73 ± 0.04583mg Gallic Acid Equivalent/g extract. The total flavonoid content of flower extract was found to be 6.0 ± 0.273 mg Quercetin Equivalent//g extract while total phenolics content was found to be 18.17 ± 0.017mg Gallic Acid Equivalent /g extract. Our study showed that S. longipedunculata leaf and flower extracts have important bioactive constituents and possess potent in vitro antioxidant activity. These parts of the plant may therefore be used as source of important pharmacological compounds for the treatment of oxidative stress related ailments